Right ventricular-vascular coupling ratio in pediatric pulmonary arterial hypertension: A comparison between cardiac magnetic resonance and right heart catheterization measurements. (15th October 2019) - Breeman, K.T.N.; Dufva, M.; Ploegstra, M.J.; Kheyfets, V.; Willems, T.P.; Wigger, J.; Hunter, K.S.; Ivy, D.D.; Berger, R.M.F.; Truong, U.
Abstract: Background: In pulmonary arterial hypertension (PAH), right ventricular (RV) failure is the main cause of mortality. Non-invasive estimation of ventricular-vascular coupling ratio (VVCR), describing contractile response to afterload, could be a valuable tool for monitoring clinical course in children with PAH. This study aimed to test two hypotheses: VVCR by cardiac magnetic resonance (VVCRCMR ) correlates with conventional VVCR by right heart catheterization (VVCRRHC ) and both correlate with disease severity. Methods and results: Twenty-seven patients diagnosed with idiopathic and associated PAH without post-tricuspid shunt, who underwent RHC and CMR within 17 days at two specialized centers for pediatric PAH were retrospectively studied. Clinical functional status and hemodynamic data were collected. Median age at time of MRI was 14.3 years (IQR: 11.1–16.8), median PVRi 7.6 WU × m 2 (IQR: 4.1–12.2), median mPAP 40 mm Hg (IQR: 28–55) and median WHO-FC 2 (IQR: 2–3). VVCRCMR, defined as stroke volume/end-systolic volume ratio was compared to VVCRRHC by single-beat pressure method using correlation and Bland-Altman plots. VVCRCMR and VVCRRHC showed a strong correlation ( r = 0.83, p < 0.001). VVCRCMR and VVCRRHC both correlated with clinical measures of disease severity (pulmonary vascular resistance index [PVRi], mean pulmonary artery pressure [mPAP], mean right atrial pressure [mRAP], and World Health Organization functional class [WHO-FC]; all p ≤ 0.02). Conclusions: Non-invasively measured VVCRCMR is feasible in pediatric PAH and comparable to invasively assessed VVCRRHC . Both correlate with functional and hemodynamic measures of disease severity. The role of VVCR assessed by CMR and RHC in clinical decision-making and follow-up in pediatric PAH warrants further clinical investigation. Highlights: Ventricular-vascular coupling ratio (VVCR) is known to predict survival in adult PH. In this multicenter study of pediatric PAH, VVCR by CMR correlates with VVCR by RHC. VVCR by CMR and by RHC correlate well with established markers of disease severity. Noninvasive VVCR by CMR warrants further studies to assess its prognostic value.